2009
DOI: 10.1139/x09-086
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cavity tree and snag abundance using negative binomial regression models and nearest neighbor imputation methods

Abstract: Cavity tree and snag abundance data are highly variable and contain many zero observations. We predict cavity tree and snag abundance from variables that are readily available from forest cover maps or remotely sensed data using negative binomial (NB), zero-inflated NB, and zero-altered NB (ZANB) regression models as well as nearest neighbor (NN) imputation methods. The models were developed and fit to data collected by the Forest Inventory and Analysis program of the US Forest Service in Washington, Oregon, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
(50 reference statements)
2
27
1
Order By: Relevance
“…Since CF resulted in unbiased estimates comparable to MSN the bad poll of RF may be ascribed to the biased variable selection of the base learners (Strobl et al 2007). Biases in RF predictions were also identified in other studies (e.g., Eskelson et al 2009;Breidenbach et al 2010).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Since CF resulted in unbiased estimates comparable to MSN the bad poll of RF may be ascribed to the biased variable selection of the base learners (Strobl et al 2007). Biases in RF predictions were also identified in other studies (e.g., Eskelson et al 2009;Breidenbach et al 2010).…”
Section: Discussionsupporting
confidence: 57%
“…In contrast to Hudak et al (2008a, b), Eskelson et al (2009) conclude that MSN is better suited for their aims compared to RF. In an application for classification purposes (Chen et al 2004), RF proved to be biased towards the most frequent classes.…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Therefore, GWR may be sufficient for the estimation of biomass per acre if that is the only variable of interest; while, the nearest neighbor imputations are preferred when multiple response variables of interest are present in the analysis. When predicting a single variable, Eskelson et al (2009b) reported that parametric methods resulted in better performance than non-parametric methods.…”
Section: Discussionmentioning
confidence: 99%
“…There are also a few studies so far have addressed this issue in forestry (e.g., Keefe, 2004;Rathbun and Fei, 2006;Eskelson et al, 2009;Flores et al, 2009;Li et al, 2011). Fortin and DeBlois (2007) applied zero-inflated Poisson model (ZIP) and zero-inflated discrete Weibull (ZIdiW) to model tree recruitment of hardwood stands.…”
Section: Introductionmentioning
confidence: 99%